New Insights into Podocyte Biology in Glomerular Health and Disease - Assady, Suheir; Wanner, Nicola; Skorecki, Karl L; Huber, Tobias B (Journal of the American Society of Nephrology, 2017)
Podocyte and glomerular research is center stage for the development of improved preventive and therapeutic strategies for chronic progressive kidney diseases. Held April 3-6, 2016, the 11th International Podocyte Conference took place in Haifa and Jerusalem, Israel, where participants from all over the world presented their work on new developments in podocyte research. In this review, we briefly highlight the advances made in characterizing the mechanisms involved in podocyte development, metabolism, acquired injury, and repair, including progress in determining the roles of genetic variants and microRNA in particular, as well as the advances made in diagnostic techniques and therapeutics.